A228 FIRST REPORT OF ADRENAL CRISIS IN TWO PATIENTS WITH EOSINOPHILIC ESOPHAGITIS. (1st March 2018) - Avinashi, V; Amed, S; Hursh, B; Chan, E
Abstract: Aims: Eosinophilic Esophagitis (EoE) is an immune mediated allergic condition affecting the esophagus. Risk factors include male sex and atopy. A treatment option is swallowed corticosteroids (cs). Patients with EoE are at risk for adrenal insufficiency (AI). We screened 14 patients on Oral Viscous Budesonide (OVB) for ≥ 3 months using the low dose ACTH stimulation test and found 6 (43%) had evidence of AI. This was found in patients with and without inhaled cs. Golekoh found 10% of their patients on Fluticasone to have AI. Methods: We present 2 cases of adrenal crisis requiring major intervention from the 'at risk' screened group. Results: Case 1 17 y.o with atopy and food allergies, diagnosed with EoE in 2011 presenting with vomiting. He was on baseline inhaled cs for asthma and cs nasal spray. OVB was successful at achieving remission and he maintained 0.5 mg po daily. Through routine screening in 2013 he was shown to be at risk of AI with an abnormal ACTH stim test result of 403 nmol/L @ 30 mins. Stress-dose cs management was taught for illnesses and stress. Despite the patient deciding to stop the OVB, he had an abnormal ACTH stim test ≥ 3 months later. Limited follow-up occurred. In June 2016, patient underwent a GA for elective surgery at an outlying hospital. No pre-operative cs were received. In recovery he had hypotension and apnea requiring a Code Blue and ICU admission. At the time, a low cortisol level was documented (44 nmol/L). He responded well to IV Hydrocortisone and was discharged the next day. A subsequent ACTH stim test was abnormal (peak 417 nmol/L). Case 2 17 y.o. ex prem with chronic lung disease, asthma, laryngeal cleft, rhinitis and food allergies. Pre-diagnosis he was on inhaled cs for asthma. He was diagnosed with EoE in 2008 presenting with dysphagia. Initially he was on Fluticasone but in 2012 was switched to 1 mg bid OVB with incomplete histological remission (some symptom improvement). He routinely underwent ACTH stim testing in 2013 and was found to have AI with a peak level of 459 nmol/L. Education was provided for episodes of moderate and severe stress. He remained on the OVB. In the interim he received stress coverage for viral meningitis in 2015 and was weaned off. He switched to Fluticasone and did not have improvement in his ACTH stim testing. In 2016 he had a URTI and took 3 po doses of cs for moderate stress. Despite the oral cs, he continued to evolve with headache, aches and weakness. Upon presentation to emergency he was hypotensive and required IV steroids and fluids. Recently, he has had difficulty weaning the cs and has shown to have low baseline cortisol production necessitating daily cs. Conclusions: Identifying EoE patients with AI is clinically relevant as they are at risk for adrenal crisis as exemplified by these two cases. The risk for AI can be enhanced by the swallowed cs, and can persist post-discontinuation. Funding Agencies: None